Stadium as An Inclusive Public Space for Resilient Community - Akhmanova, Irina (MAJ - Malaysia Architectural Journal, 2025)
This paper analyses sports stadiums’ ongoing transformation and surrounding areas in Asian urban landscapes, specifically focusing on notable examples like KL Sports City and Kai Tak. The role of these stadiums is shifting from traditional sports venues to multifaceted urban elements that align with the evolving needs of contemporary urban development, driven by changing demographics, notably ageing populations, and increasing demands for inclusivity, equity, and accessibility in public spaces. As a result, sports complexes are now being designed as vibrant community hubs that extend beyond hosting major sports events, incorporating retail and community zones, educational facilities, and medical services, contributing to the creation of sustainable neighbourhoods and resilient urban communities. This transformation is grounded in universal design principles, ensuring accessibility and inclusivity for diverse users. The study examines how thoughtful public area design engages the broader population in active lifestyles, investigating strategies to promote inclusivity and accessibility. By analyzing best practices and the shifts in public and sports areas within these facilities, this research offers valuable insights into the changing nature of sports stadiums, proposing innovative approaches to design and management that highlight their potential to enhance urban life beyond their traditional function, ultimately presenting a forward-looking perspective on the integration of sports stadiums into the urban fabric.